SIRIP PENDINGIN (FIN) TAMBAHAN UNTUK MENINGKATKAN STABILITAS AERODINAMIKA DAN EFEKTIVITAS PERPINDAHAN PANAS PADA SEPEDA MOTOR - Handayanto, Rahmadya Trias; Hidayat, Wahyu; ., Herlawati (RESULTAN : Jurnal Kajian Teknologi, 2011)
There are two problems when motorbike running at high speed: the aerodynamic effect and over heating of the engine. As a two wheels vehicle, motorbike must keep the tyre at the road to avoidfrom accident. When it runs at high speed, the aeorodynamic factor must be counted. If there is a different from upper and lower air speed of a plat, there must be a force to it. It is very dangerous if the force is lift force because it make the traction of tyre down, so in this research I propose additional design for this purpose. Not only for stabilisation of vehicle, this propose design also has a function as a fin for heat exchanger from engine to air. Analysis by Computational Fluid Dynamics (CFD) to my propose design was adequate for aerodynamic and heat transfer analysis